2014
DOI: 10.1371/journal.pone.0113933
|View full text |Cite|
|
Sign up to set email alerts
|

Observational Study Assessing Demographic, Economic and Clinical Factors Associated with Access and Utilization of Health Care Services of Patients with Multiple Sclerosis under Treatment with Interferon Beta-1b (EXTAVIA)

Abstract: Multiple sclerosis (MS) results in an extensive use of the health care system, even within the first years of diagnosis. The effectiveness and accessibility of the health care system may affect patients' quality of life. The aim of the present study was to evaluate the health care resource use of MS patients under interferon beta-1b (EXTAVIA) treatment in Greece, the demographic or clinical factors that may affect this use and also patient satisfaction with the health care system. Structured interviews were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Data concerning the prevalence of unemployment among workers with MS were reported from 29 countries. Austria [ 39 ], Czech Republic [ 40 ], Greece [ 41 ], Hungary [ 42 ], Kuwait [ 43 ], Portugal [ 44 ], Russia [ 45 ], and Argentina [ 46 ] each contributed with one (0.6%) publication reporting the prevalence of unemployed subjects. Ireland [ 47 , 48 ], Israel [ 49 , 50 ], Poland [ 51 , 52 ], and Saudi Arabia [ 53 , 54 ] contributed with two (1.3%) studies each while Brazil [ 55 57 ], Iran [ 58 – 60 ], Holland [ 61 63 ], Norway [ 11 , 64 , 65 ], and Switzerland [ 66 68 ] contributed with three (2.0%) studies each.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data concerning the prevalence of unemployment among workers with MS were reported from 29 countries. Austria [ 39 ], Czech Republic [ 40 ], Greece [ 41 ], Hungary [ 42 ], Kuwait [ 43 ], Portugal [ 44 ], Russia [ 45 ], and Argentina [ 46 ] each contributed with one (0.6%) publication reporting the prevalence of unemployed subjects. Ireland [ 47 , 48 ], Israel [ 49 , 50 ], Poland [ 51 , 52 ], and Saudi Arabia [ 53 , 54 ] contributed with two (1.3%) studies each while Brazil [ 55 57 ], Iran [ 58 – 60 ], Holland [ 61 63 ], Norway [ 11 , 64 , 65 ], and Switzerland [ 66 68 ] contributed with three (2.0%) studies each.…”
Section: Resultsmentioning
confidence: 99%
“…32, 120, 122, 123], Denmark (four, 6.0%) [73][74][75][76], Australia (three, 4.5%) [108,109,175], Belgium (three, 4.5%) [35,79,80], Holland (three, 4.5%) [61,63,176], Italy (three, 4.5%) [111 -113], Ireland (two, 3.0%) [47,48], Spain (two, 3.0%) [8, 28], Sweden (two, 3.0%) [90,91], Switzerland (two, 3.0%) [66,67], Argentina (one, 1.5%) [46], Austria (one, 1.5%) [39], Brazil (one, 1.5%) [55], the Czech Republic (one, 1.5%) [40], France (one, 1.5%) [85], Greece (one, 1.5%) [41], Hungary (one, 1.5%) [42], Iran (one, 1.5%) [59], Israel (one, 1.5%) [49], Russia (one, 1.5%) [45], Norway (one, 1.5%) [65], and Portugal (one, 1.5%) [44]. One (1.5%) study was multinational [170].…”
Section: Plos Onementioning
confidence: 99%
“…In our survey, patients with lower intellectual capacity or from lower socioeconomic classes were indicated as more likely to have poor treatment adherence, which is consistent with previous reports. 15 , 16 Furthermore, higher levels of nonadherence have also been reported more among depressed and despairing MS patients. 8 …”
Section: Discussionmentioning
confidence: 99%
“…Hadjigeorgiou et al reported that 58.89% of MS patients who are employed, had been absent from work due to problems with health services. [33] is means that the disease is going to carry an extra burden to the economy by taking away years of productivity that MS patients would have contributed.…”
Section: Discussionmentioning
confidence: 99%